Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 29 Jun 2016, 06:11

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If r = (3p + q)/2 and s = p q, for which of the following

Author Message
Manager
Joined: 03 Mar 2007
Posts: 163
Followers: 1

Kudos [?]: 19 [0], given: 0

If r = (3p + q)/2 and s = p q, for which of the following [#permalink]

### Show Tags

24 May 2007, 15:01
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

If r = (3p + q)/2 and s = p – q, for which of the following values of p would r^2 = s^2 ?

a) 1/5q
b) 10 - (3/2q)
c) q - 1
d) 3q
e) (9/2q) - 9
GMAT Club Legend
Joined: 10 Apr 2007
Posts: 4318
Location: Back in Chicago, IL
Schools: Kellogg Alum: Class of 2010
Followers: 89

Kudos [?]: 746 [0], given: 5

### Show Tags

24 May 2007, 15:50
since r^2 = s^2 |r| = |s|

replace r with |p - q|

|p - q| = (3p + q)/2

2p - 2q = 3p + q

p = -3q

Since its the absolute value of s the answer is:

d) 3q
Manager
Joined: 03 Mar 2007
Posts: 163
Followers: 1

Kudos [?]: 19 [0], given: 0

### Show Tags

24 May 2007, 19:18
correct answer is actually A, not sure how to get it since there is no explanation.
Manager
Joined: 03 Mar 2007
Posts: 163
Followers: 1

Kudos [?]: 19 [0], given: 0

### Show Tags

24 May 2007, 19:23
riverripper wrote:
since r^2 = s^2 |r| = |s|

replace r with |p - q|

|p - q| = (3p + q)/2

2p - 2q = 3p + q

p = -3q

Since its the absolute value of s the answer is:

d) 3q

One problem I have with this:

If it is an absolute value then,

|p - q| = (3p + q)/2

OR

|p - q| = -[(3p + q)/2] = (-3p - q)/2

p - q = (-3p - q)/2

2p - 2q = -3p - q
q = 5p

p = 1/5q

Guess I answered my own question

I think D is put in as a trick answer.
Manager
Joined: 19 Aug 2006
Posts: 217
Followers: 1

Kudos [?]: 26 [0], given: 0

Re: From the web - need help [#permalink]

### Show Tags

25 May 2007, 06:50
salr15 wrote:
If r = (3p + q)/2 and s = p – q, for which of the following values of p would r^2 = s^2 ?

a) 1/5q
b) 10 - (3/2q)
c) q - 1
d) 3q
e) (9/2q) - 9

Its A.

(There is a mistake in option A, option should be q/5 and not 1/5q)

Solve from the options.

Put the value of p = q/5 and solve for r and s; the value will be 4q/5

for both r and s.
Manager
Joined: 03 Mar 2007
Posts: 163
Followers: 1

Kudos [?]: 19 [0], given: 0

### Show Tags

25 May 2007, 07:36
sorry that was a typo by me, should be (1/5)q and not 1/5q.
Intern
Joined: 05 Jun 2003
Posts: 48
Followers: 0

Kudos [?]: 0 [0], given: 0

Re: From the web - need help [#permalink]

### Show Tags

25 May 2007, 08:26
salr15 wrote:
If r = (3p + q)/2 and s = p – q, for which of the following values of p would r^2 = s^2 ?

a) 1/5q
b) 10 - (3/2q)
c) q - 1
d) 3q
e) (9/2q) - 9

I got A.

Solve for p when r^2=s^2, which is same as [(3p+q)/2]^2 = (p-q)^2
--> (9p^2+6pq+q^2)/4 = p^2-2pq+q^2 *multiply 4 on both sides*
--> 9p^2+6pq+q^2 = 4p^2-8pq+4q^2 *simplify*
--> 5p^2+14pq-3q^2=0 *factor*
--> (5p-q)*(p+3q)=0 *solve*
--> p=q/5 OR p=-3q

Since -3q isn't in one of the answer choices, the answer must be A.
Re: From the web - need help   [#permalink] 25 May 2007, 08:26
Display posts from previous: Sort by